Sentence Studies in Indonesian Research Articles from the History and Law Disciplines - Warsidi Warsidi (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
Studies on sentences have been conducted in many linguists' academic works, but only a few of them investigate this area in research articles. Besides, sentence studies in Indonesian research articles have received a very small portion of academic attention. For this reason, the present study intends to investigate words and sentences, as well as voice forms in Indonesian research articles to provide a more comprehensive understanding to students and novice authors. The data in the present study are 30 Indonesian research articles from the disciplines of History and Law. The analysis used a top-down approach, combining a computer analysis system and manual analysis. An earlier analytical approach was employed and the results indicate that both data sets share similarities and differences. Their similarities and differences are presented in both the result section and the discussion section.